Rapamycin Enhances Mitophagy and Attenuates Apoptosis After Spinal Ischemia-Reperfusion Injury - Li, Qiang; Gao, Shane; Kang, Zhanrong; Zhang, Meiyan; Zhao, Xin; Zhai, Yu; Huang, Jianming; Yang, Guo-Yuan; Sun, Wanju; Wang, Jian (Frontiers in Neuroscience, 2018)
Spinal cord is extremely vulnerable to ischemia-reperfusion (I/R) injury, and mitochondrion is the most crucial interventional target. Rapamycin can promote autophagy and exert neuroprotective effects in several diseases of the central nervous system. However, the impact of rapamycin via modulating mitophagy and apoptosis by after spinal cord ischemia-reperfusion injury remains unclear. This study was undertaken to investigate the potential role of rapamycin in modulating mitophagy and mitochondria-dependent apoptosis using the spinal cord ischemia-reperfusion injury (SCIRI) mouse model. We found that rapamycin significantly (p<0.05) enhanced mitophagy via increasing the translocation of p62 and Parkin to the damaged mitochondria in the mouse spinal cord injury model. Meanwhile, rapamycin significantly (p<0.05) decreased mitochondrial apoptosis related proteins (Apaf-1, Caspase-3, Caspase-9) expression via inhibiting Bax translocation to mitochondria and cytochrome c release from mitochondria . After 24 hours following SCIRI, rapamycin treatment apparently reduced TUNEL+ cells in spinal cord ischemic tissue and improved locomotor function in these mice. Thus, our results demonstrate that rapamycin can improve the locomotor function via promoting mitophagy and attenuating SCIRI -induced apoptosis, indicating its potential therapeutic application against spinal cord injury.